Characteristic approach for the treatment of perioral dermatitis - Mithilesh, Burra; Vamsi, Varahabhatla (Запорізький державний медичний університет, 2017)
Introduction: Perioral dermatitis is a chronic papulopustular facial dermatitis which mostly occurs in women aging 20-45 years and children and is multifactorial in etiology. Symptoms may consist of a sensation of stinging and burning.
Keywords: тези